The implications of the sharing economy for transport. Issue 2 (4th March 2019) - Standing, Craig; Standing, Susan; Biermann, Sharon
ABSTRACT: The sharing economy has gained a lot of attention in recent years. Despite the substantial growth in shared services, its impact overall on transport is unclear. This paper analyses the literature on sharing in transport and includes government and consultant reports, websites and academic journals. The drivers of ride-sharing, car-sharing, car-pooling and freight-sharing are largely economic and convenience related for participants. Trust, technology platforms and the trend to avoid ownership of assets are facilitating factors in its growth. Over-regulation, inconsistent quality of service and the need for recommendation are potential barriers. The transport journals in particular are relatively slow to research this topic with more focusing on bike-sharing than other modes of vehicle sharing. The paper discusses the impact of sharing on transport suggesting it is likely to be part of a solution to transport problems and congestion perhaps in combination with other developments such as driverless vehicles. It also warns of the dangers of over-regulation and under-regulation. The future will require holistic transport strategies that consider sharing options and will require government departments to work cooperatively.